2018
DOI: 10.1101/293464
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using citizen science data in integrated population models to inform conservation decision-making

Abstract: Analysis of animal population status and change are core elements of ecological research and critical for prioritizing conservation actions. Traditionally, count-based data from structured surveys have been the main source of information used to estimate trends and changes in populations. In the past decade, advances in integrated population models (IPMs) have allowed these data to be combined with other data sources (e.g., observations of marked individuals).IPMs have allowed researchers to determine the dire… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
0
9
1
Order By: Relevance
“…However, the 5% annual decrease in colony size observed during this study was statistically indistinguishable from the 6% decline in overall abundance recently reported from a study (Robinson et al 2018) that analyzed completely different count data from the eBird program (Sullivan et al 2014). The similarity in annual declines across the two studies suggest that tricolored blackbird population decline is occurring through a decline in colony size, possibly more so than a decline in colony number.…”
Section: Management Implicationscontrasting
confidence: 47%
See 1 more Smart Citation
“…However, the 5% annual decrease in colony size observed during this study was statistically indistinguishable from the 6% decline in overall abundance recently reported from a study (Robinson et al 2018) that analyzed completely different count data from the eBird program (Sullivan et al 2014). The similarity in annual declines across the two studies suggest that tricolored blackbird population decline is occurring through a decline in colony size, possibly more so than a decline in colony number.…”
Section: Management Implicationscontrasting
confidence: 47%
“…The similarity in annual declines across the two studies suggest that tricolored blackbird population decline is occurring through a decline in colony size, possibly more so than a decline in colony number. The integrated population model analysis by Robinson et al (2018) combined eBird relative abundance data with independent data on productivity and survival. Correlations between population growth rates and vital rates suggested that population growth was especially sensitive to adult female survival and productivity (Robinson et al 2018).…”
Section: Management Implicationsmentioning
confidence: 99%
“…Such methods have only recently been introduced in ecology and present computational and analytical challenges (e.g., accounting for sampling biases from volunteer‐collected data; Sullivan et al. ), but offer potentially powerful avenues for incorporating “big data”, such as opportunistic species sightings by the public (e.g., eBird), into integrated modeling frameworks (Robinson et al., in press ). Similarly, eliciting expert opinion can be a useful approach in cases where deficient data prohibit the ability to build reliable statistical models.…”
Section: Discussionmentioning
confidence: 99%
“…, Robinson et al. ). Weekly estimates of relative abundance enable prioritization to explicitly consider the dynamic nature of species’ populations and to identify sites with high proportions of species’ populations.…”
Section: Introductionmentioning
confidence: 99%
“…To fill this gap, we use weekly estimates of shorebird relative abundance (hereafter, abundance) across the Americas, derived from eBird data (Sullivan et al 2014). eBird data include curated and reviewed contributions from citizen scientists and some professional surveys, and have been used to derive species' distributions and inform conservation action , Reynolds et al 2017, Sullivan et al 2017, Robinson et al 2018. Weekly estimates of relative abundance enable prioritization to explicitly consider the dynamic nature of species' populations and to identify sites with high proportions of species' populations.…”
Section: Introductionmentioning
confidence: 99%